Emergence of CTX-M Group 1-ESBL producing Klebsiella pneumonia from a tertiary care centre in Karachi, Pakistan - Khan, Erum; Schneiders, Thamarai; Zafar, Afia; Aziz, Erum; Parekh, Asra; Hasan, Rumina (The Journal of Infection in Developing Countries, 2010)
Background: Extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae have been reported previously from Pakistan but the genotypic characteristics of these enzymes is not known. Hence the aim of the study was first to characterise the genotypic content of these beta-lactamases and secondly to assess the clonal relationship of these isolates. Methodology: We analysed 65 non-duplicate ESBL positive, K. pneumoniae isolates prospectively collected based on phenotype as detected using the two-disc method. Isolates were collected from different sources: blood cultures (46.15%; n = 30); tracheal aspirates (24.6%; n = 16); urine (10.7%; n = 7); wound swabs, pus and tissue (18.4%; n = 12). ESBL production was confirmed by the ESBL E-test method and the presence of the blaCTX-M encoding genes was confirmed by polymerase chain reaction. The clonal relationship of clinical isolates was studied by Pulsed Field Gel Electrophoresis. Results: The results showed that 93.84% (n = 61) isolates of K. pneumoniae were positive for the blaCTX-M-1 group. One isolate showed PCR signals for blaCTX-M-25 group. None of our isolates were positive for CTX-M groups 2, 8 and 9. The majority of blaCTX-M positive isolates were genetically unrelated and no epidemic clones were identified. Conclusion: This study reports the emergence of CTX-M groups 1 and 25 producing isolates of K. pneumoniae with genetic diversity in Karachi, Pakistan.